Synthesis and Characterization of Rare Earth Barium Copper Oxide [(RE₁₋xMx)Ba₂Cu₃O₇₋d] via Coprecipitation and Electrophoretic Deposition Methods - Wahid, Mohd Haniff (2010)
Preparation of superconducting material was usually carried out via the solid state reaction technique where oxides and carbonates metal precursors were mixed thoroughly followed by heat treatment. Alternatively, the materials can be prepared via the wet chemistry technique, in which higher homogeneity could be achieved due to initial mixture of cations at atomic scale. In this study, superconductors were prepared via co-precipitation technique from metal acetates which were reacted with oxalic acid as a precipitating agent to form metal oxalates. Transmission Electron Microscopy (TEM) analysis shows that ultra fine powders of metal oxalates were obtained with the particle size in the range of 9 to 12 nanometers. X-ray diffraction (XRD) analyses confirmed the phases of the metal oxalates. Thermal decomposition and phase formation stages of samples were determined via Thermogravimetric (TG), Differential Thermal Analysis (DTA) and XRD analysis at different heat treatment temperatures. Minute traces of BaCuO2 phase was discernible in the X-ray diffraction patterns of sample obtained after sintering at 880 oC for 15 hours. By increasing the sintering temperature up to 970 oC, elimination of the BaCuO2 phase in YNdBCO samples has succeeded. However, this phase remained in YGdBCO and NdGdBCO samples. Electrical resistivity measurement via 4-point probe technique shows zero resistance temperature, TC(R=0) and TC-onset are (86 K, 95 K), (88 K, 92 K) and (90 K, 98 K) for samples YNdBCO, YGdBCO and NdGdBCO, respectively. In addition, preparation of superconductor coating were also carried out in this study. Numerous efforts have been reported in fabricating superconductors into certain shapes namely, wires, thin films and many more. The Electrophoretic Deposition (EPD) method is an attractive method where it is low cost, requires simple apparatus, large surface area with uniform thickness of deposits could be obtained and deposits could be designed according to the shape of substrate. In this study, the superconductor coatings were prepared via the EPD method. Several parameters such as colloidal suspension behaviour, voltage of deposition, grinding time, substrate and sintering conditions were investigated in order to obtain good quality coatings. Colloidal suspension behaviour was investigated via Nanophox particle size analyzer. Smallest particle size distribution was ~ 15 nm by dispersing in acetone. Meanwhile, in order to enhance the deposition of the powders, particle size of the powders need to be reduced. After grinding the powders, deposition was improved and TEM analysis shows that deposited powders are in the range f 30 – 40 nm. To avoid the melting of silver substrates, sintering in argon atmosphere was carried out followed by slow cooling in oxygen atmosphere. XRD analyses of deposited samples show that orthorhombic 123 phase was obtained YBCO, GdBCO and NdBCO samples however, for YBCO samples the orthorhombicity value was relatively low. Meanwhile, improvement in microstructure was achieved where more dense films were successfully obtained by performing the multi-deposition technique.